A Exploratory Study to Assess the Food Choices among College Students of Pune City - Sharadha Ramesh; Poonam Yadav; Shruti Dabhade (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Students studying in college make poor dietary choices which causes significant healthproblems to their health. Various students have their meals in the dining facilities of college were theyhave limited healthy food options.1,2,3 If the students will not gain the adequate nutritional on daily basisthis will be effect there academic and physical performance. The purpose of this study was to identify thefood choices opted by the college students. Objectives of the Study: To assess the food choices amongcollege students of Pune City.2. To associate the selected demographic variables with the food choicesamong college students of Pune City. Methodology: Quantitative research approach was adopted for thisstudy to accomplish the objectives of the study. In this study, Non-experimental Descriptive survey designwas used. The investigator conducted the study in urban area of Pune City. In the present study, the collegestudents of Pune City. Who fulfilled the inclusive criteria were the samples. The sample size was 221.Result: The result of the above study reveals that the college students have and habit of consuming fastfood during their lunch meal. During breakfast most of them take beverages and do not prefer fast food andmajority of them almost take the full meal .It can be identified that they eat only one health meal duringtheir dinner which is not enough for the students to fulfill their nutritional requirement of the day. Manystudents eat fast food and also there consumption of fast food was also very high and most of them eat thisfast food during their lunch meal which is not good for their health. Future research and awareness shouldbe created among college students to make them aware about the healthy eating habits and food which canbe implemented in their diet in daily meals